A Hydrogeomechanical Study Of Overburden Aquifer Response To Longwall Mining - G. J. Hasenfus (International Conference on Ground Control in Mining, 1988)
This paper presents the results of an extensive hydrological and geomechanical monitoring program which Gas conducted at a longwall coal mine in W. Va. The field program included monitoring of groundwater levels. overburden hydraulic conductivity, overburden movement, and surface subsidence relative to the passage of the longwall. Overburden geology and rock strength characteristics were evaluated prior to mining. A postmining corehole was drilled to evaluate main roof fracturing. An overburden response model is proposed based on the correlations between hydrological and geomechanical data.